Implementasi Minyak Wijen Sebagai Bahan Bakar Alternatif Untuk Kendaraan Matic Terhadap Pelaku Bengkel Di Sambi Kerep Surabaya - Setyono, Gatot; Kholili, Navik; Khusna, Dwi (Fakultas Teknik-Universitas Wijaya Putra, 2022)
Biofuels include energy-enriched chemicals produced directly through biological processes or derived from the chemical conversion of the biomass of previously living organisms. Biofuels can be classified into two categories: primary and secondary biofuels. The main biofuels are produced directly from burning woody plant material or cellulose and dry animal dung. Secondary biofuels can be classified into three generations, and each is produced indirectly from plant and animal materials. The first-generation biofuel is ethanol derived from starch-rich food crops or biodiesel, extracted from animal fat wastes such as cooking oil. The second generation is bioethanol derived from non-food cellulosic biomass and biodiesel derived from oil-rich plant seeds such as soybean or jatropha. The third generation is a biofuel produced from cyanobacteria, microalgae, and other microbes, which is the most promising approach to meet global energy demand. This community service aims to explain innovation and provide knowledge to technology players, namely technicians, operators, supervisors, and workshop supervisors, about the use of alternative fuels of sesame oil for small-capacity automatic gasoline engines. The counseling results show that the performance and exhaust gas results are optimal so that the technology actors know the quality and quantity of the alternative energy.